Volume 7: Turbomachinery, Parts A, B, and C 2010
DOI: 10.1115/gt2010-22840
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Inflow Conditions on the Heavy-Duty Gas Turbine Exhaust Diffusers Performance

Abstract: The flow in exhaust diffusers along with the channel geometry strongly depends on the inflow conditions, including Mach number level, total pressure distribution, flow angle, and turbulence. In the first part of this paper, the impact of these parameters is analyzed using CFD, experimental data from the test rig and field measurements. A widespread opinion is that the optimal condition for the diffuser is an axial uniform inflow. However, it is shown in this paper that non-uniform pressure distribution as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The results showed that for the given diffuser configuration, the pressure recovery of volute diffusers is basically independent from the inlet Mach number, but varies considerably with the inlet swirl, and the reason for the dependency is related to the flow separation at the struts, caused by the different incidence angles. The subsequent investigations of Vassiliev et al 14 and Dong et al 15 have further indicated that the nonuniform inlet pressure distribution, as compared to a uniform one, can lead to better volute diffuser performances, and the moderate residual swirl can improve the volute aerodynamic performance significantly.…”
Section: Effect Of Turbine Exit Conditions Simulated On the Nonaxisymmetric Exhaust Volutementioning
confidence: 98%
“…The results showed that for the given diffuser configuration, the pressure recovery of volute diffusers is basically independent from the inlet Mach number, but varies considerably with the inlet swirl, and the reason for the dependency is related to the flow separation at the struts, caused by the different incidence angles. The subsequent investigations of Vassiliev et al 14 and Dong et al 15 have further indicated that the nonuniform inlet pressure distribution, as compared to a uniform one, can lead to better volute diffuser performances, and the moderate residual swirl can improve the volute aerodynamic performance significantly.…”
Section: Effect Of Turbine Exit Conditions Simulated On the Nonaxisymmetric Exhaust Volutementioning
confidence: 98%
“…[18][19][20][21][22] These investigations include the effect of Mach and Reynolds number, total pressure and temperature distribution, flow angle, and turbulence. The systematic review of all these effects is provided in Vassiliev et al 23 From their studies, it is known that the performance of the diffusers is influenced by the inflow conditions.…”
Section: Introductionmentioning
confidence: 99%